1999
DOI: 10.1093/humrep/14.9.2200
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotrophin and testosterone suppression by 7α-methyl-19-nortestosterone acetate administered by subdermal implant to healthy men

Abstract: The synthetic androgen 7alpha-methyl-19-nortestosterone (MENT) is a potent suppressor of gonadotrophin that has several advantages for long term administration to normal or hypoandrogenic men. The aim of this study was to examine MENT serum concentrations following subdermal insertion of MENT acetate (MENT Ac) implants and their effects on gonadotrophins, testosterone, dihydrotestosterone (DHT), sex hormone-binding globulin, prostate specific antigen and insulin-like growth factor-1 serum concentrations in nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…In vivo MENT Ac release rate was estimated from recovered implants, following the extraction procedure described by Noe et al (17). Monthly postremoval visits continued until sperm concentrations returned to 20 million/ml or higher.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo MENT Ac release rate was estimated from recovered implants, following the extraction procedure described by Noe et al (17). Monthly postremoval visits continued until sperm concentrations returned to 20 million/ml or higher.…”
Section: Methodsmentioning
confidence: 99%
“…7␣-Methyl-19-nortestosterone (MENT) is a synthetic androgen that is more potent than T for gonadotropin suppression and is resistant to 5␣-reduction, with potential advantages when used as a contraceptive (15)(16)(17). MENT acetate (Ac) has diffusion characteristics that are well suited for delivery via subdermal implants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…#E-8875) (Sigma, St. Louis, MO) to ethylene and vinyl acetate (EVA) tubing (Elvax 770, 9% VA; 2.15 mm ID Â 2.4 mm OD, DuPont, Wilmington, DE). Earlier studies have estimated that implants using EVA had a steroid (e.g., MENT, 7a-methyl-19-nortestosterone) release rate of 90 mg/cm/day in vivo (in humans) when placed under the skin (Noe et al, 1999;von Eckardstein et al, 2003) versus $30 mg/cm/day for Silastic implants (Kincl et al, 1968;Robaire et al, 1979). Both ends of the EVA tubing were sealed by heat using a soldering iron (Cat.…”
Section: Preparation Of Steroid Implantsmentioning
confidence: 99%
“…Earlier studies have shown that implants using EVA had a steroid release rate (e.g. of 7 -methyl-19-nortestosterone) of 90 µg/cm/day in vivo when placed under the skin in humans (Noe et al 1999, von Eckardstein et al 2003. Animal surgery was performed in adult rats (400 g bw) under anesthesia using ketamine HCl at 60 mg/kg bw (i.m.).…”
Section: Preparation Of Steroid Implants and Their Placement Subdermamentioning
confidence: 99%